Plant phenology and species-specific traits control plant CH4 emissions in a northern boreal fen - Ge, Mengyu; Korrensalo, Aino; Laiho, Raija; Lohila, Annalea; Mäkiranta, Päivi; Pihlatie, Mari; Tuittila, Eeva-Stiina; Kohl, Lukas; Putkinen, Anuliina; Koskinen, Markku (Wiley, 2024)
Aerenchymatic transport is an important mechanism through which plants affect methane (CH4) emissions from peatlands. Controlling environmental factors and the effects of plant phenology remain, however, uncertain.We identified factors controlling seasonal CH4 flux rate and investigated transport efficiency (flux rate per unit of rhizospheric porewater CH4 concentration). We measured CH4 fluxes through individual shoots of Carex rostrata, Menyanthes trifoliata, Betula nana and Salix lapponum throughout growing seasons in 2020 and 2021 and Equisetum fluviatile and Comarum palustre in high summer 2021 along with water-table level, peat temperature and porewater CH4 concentration.CH4 flux rate of C. rostrata was related to plant phenology and peat temperature. Flux rates of M. trifoliata and shrubs B. nana and S. lapponum were insensitive to the investigated environmental variables. In high summer, flux rate and efficiency were highest for C. rostrata (6.86 mg m(-2) h(-1) and 0.36 mg m(-2) h(-1) (mu mol l(-1))(-1), respectively). Menyanthes trifoliata showed a high flux rate, but limited efficiency. Low flux rates and efficiency were detected for the remaining species.Knowledge of the species-specific CH4 flux rate and their different responses to plant phenology and environmental factors can significantly improve the estimation of ecosystem-scale CH4 dynamics in boreal peatlands. Peer reviewed